Epigenetic strategies synergize with PD-L1/PD-1 targeted cancer immunotherapies to enhance antitumor responses - Xi Chen (Acta Pharmaceutica Sinica B, 2020)
Immunotherapy strategies targeting the programmed cell death ligand 1 (PD-L1)/programmed cell death 1 (PD-1) pathway in clinical treatments have achieved remarkable success in treating multiple types of cancer. However, owing to the heterogeneity of tumors and individual immune systems, PD-L1/PD-1 blockade still shows slow response rates in controlling malignancies in many patients. Accumulating evidence has shown that an effective response to anti-PD-L1/anti-PD-1 therapy requires establishing an integrated immune cycle. Damage in any step of the immune cycle is one of the most important causes of immunotherapy failure. Impairments in the immune cycle can be restored by epigenetic modification, including reprogramming the environment of tumor-associated immunity, eliciting an immune response by increasing the presentation of tumor antigens, and by regulating T cell trafficking and reactivation. Thus, a rational combination of PD-L1/PD-1 blockade and epigenetic agents may offer great potential to retrain the immune system and to improve clinical outcomes of checkpoint blockade therapy.